A comprehensive simulation program for modified atmosphere and humidity packaging (MAHP) of fresh fruits and vegetables. (August 2017) - Jalali, Ali; Seiiedlou, Sadegh; Linke, Manfred; Mahajan, Pramod
Abstract: Modified atmosphere and humidity packaging (MAHP) is used to extend shelf life and maintaining the quality of fresh fruits and vegetables by modifying desired gas concentration and relative humidity (RH) inside fresh produce package. Several factors affect the optimum design of MAHP, most of which are time and or temperature dependent. Hence, there is a vital need for a simulation tool that includes all affecting parameters and their interactive behavior on package gas composition and water vapour. In this study a comprehensive simulation program based on integrative mathematical modeling is presented. A number of validation experiments were conducted to evaluate the robustness of the simulation program under constant and varying temperature conditions during storage period and predict gas composition, humidity and moisture condensation dynamics in packaged strawberry and plum. The simulated results were satisfactory with those obtained experimentally. The validated simulation program was then used for optimization of modified humidity packaging for both plum and strawberry. The predicted equilibrium headspace humidity was 94.0 and 98.8% for strawberries and plums, respectively which was very close to measured values of 93.5 and 94.1%, respectively. Therefore, the simulation program was found to be a convenient tool to virtually test the package under a broad range of environmental conditions such as temperature and RH resembling real supply chain conditions and ensure proper selection of packaging systems for the optimum performance. Highlights: A simulation program for designing MAHP of fresh produce was developed. A broad range of designing aspects was considered in mathematical modeling procedure. Simulation results validated successfully for two different products. The program is a promising alternative of experimental procedures of MAHP design.